2013
DOI: 10.1016/j.clinbiochem.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, sensitive and simultaneous determination of ascorbic and uric acids in human plasma by ion-exclusion HPLC-UV

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. Objectives: Ascorbic (AA) and uric (UA) acids act as antioxidants and are capable to react with biologically rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…1b inset illustrated that this chemosensor exhibited a linear response toward negative logarithm of AsA concentration from 80 nM to 50 μM, the linear equation was y¼2915-381.4x and the linear relative coefficient was R 2 ¼ 0.993. The detection limit of AsA was estimated to 20 nM, which is lower than the AsA concentration detected by previous researches [15,28] in physiological sample. We also compared our technique with other methods (Table S1), and the results showed that our chemosensor provided lower detection limit and wider line range for the detection of AsA.…”
Section: Chemical Properties Of Spin-labeled Fluorescence Probementioning
confidence: 86%
See 1 more Smart Citation
“…1b inset illustrated that this chemosensor exhibited a linear response toward negative logarithm of AsA concentration from 80 nM to 50 μM, the linear equation was y¼2915-381.4x and the linear relative coefficient was R 2 ¼ 0.993. The detection limit of AsA was estimated to 20 nM, which is lower than the AsA concentration detected by previous researches [15,28] in physiological sample. We also compared our technique with other methods (Table S1), and the results showed that our chemosensor provided lower detection limit and wider line range for the detection of AsA.…”
Section: Chemical Properties Of Spin-labeled Fluorescence Probementioning
confidence: 86%
“…A number of specific assays for reductants including ascorbic acid, uric acid, tocopherol etc. have been developed based on high performance liquid chromatography (HPLC) [15,16]. These techniques require several complicated preliminary steps.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the course of typical gout passes through four stages: asymptomatic hyperuricemia, acute gouty inflammation, intermittent gout and chronic tophaceous gout (Guggi et al, 2002;Liu et al, 2011). It is mainly excreted in the urine (Huda et al, 2014;Ferin et al, 2013). Because it is possible to prevent hyperuricemia by making lifestyle improvements, early detection and treatment are important (Matsuura, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, monitoring the concentration of UA in bodily fluids is essential in diagnosis and treatment of the corresponding diseases. Many methods have been reported for the determination of UA, such as capillary electrophoresis (CE) [7], enzymatic assay (EA) [8], high-performance liquid chromatography (HPLC) [9, 10], differential pulse voltammetric (DPV) [11, 12], and UV-Vis spectroscopy [13, 14]. Chemiluminescence (CL) has also been developed for UA determination [1517].…”
Section: Introductionmentioning
confidence: 99%